Autonomous microlasers for profiling extracellular vesicles from cancer spheroids - Wang, Ziyihui (2023)
Self-propelled micro/nanomotors are emergent intelligent sensors for analyzing extracellular biomarkers in circulating biological fluids. Conventional luminescent motors are often masked by a highly dynamic and scattered environment, creating challenges to characterize biomarkers or subtle binding dynamics. Here we introduce a strategy to amplify subtle signals by coupling strong light-matter interactions on micromotors. A smart whispering-gallery-mode microlaser that can self-propel and analyze extracellular biomarkers is demonstrated through a liquid crystal microdroplet. Lasing spectral responses induced by cavity energy transfer were employed to reflect the abundance of protein biomarkers, generating exclusive molecular labels for cellular profiling of exosomes derived from 3D multicellular cancer spheroids. Finally, a microfluidic biosystem with different tumor-derived exosomes was employed to elaborate its sensing capability in complex environments. The proposed autonomous microlaser exhibits a promising method for both fundamental biological science and applications in drug screening, phenotyping, and organ-on-chip applications.